2017
DOI: 10.1111/ijac.12809
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic perspective of Sr‐related degradation issues in SOFCs

Abstract: La,Sr)(Co,Fe)O 3-d is very common as cathode material in SOFC applications. Sr in this type of cathode material is very reactive to form secondary phases with other oxides, which affect micro-structures and properties of the cathode materials, GDC layers and ZrO 2 -based electrolytes. The Sr-related degradation issues, Cr poisoning and volatile Sr species formation, are studied. As supplement to existing experimental knowledge on Cr poisoning, specific thermodynamic aspects for Cr poisoning are discussed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…The diffusion of Sr across the GDC layer is mainly caused by the high reactivity of segregated Sr species. Thermodynamically, surface-segregated Sr species exist mainly in the form of Sr(OH) 2 in humid air that is volatile under SOFC operating conditions [251]. Because of this, volatile Sr species can easily diffuse across the pores or grain boundaries of GDC barrier layers through gas-or solid-phase diffusion to reach the YSZ surface and form SrZrO 3 [56,252].…”
Section: Sr Segregation and Reaction At Ysz/gdc Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion of Sr across the GDC layer is mainly caused by the high reactivity of segregated Sr species. Thermodynamically, surface-segregated Sr species exist mainly in the form of Sr(OH) 2 in humid air that is volatile under SOFC operating conditions [251]. Because of this, volatile Sr species can easily diffuse across the pores or grain boundaries of GDC barrier layers through gas-or solid-phase diffusion to reach the YSZ surface and form SrZrO 3 [56,252].…”
Section: Sr Segregation and Reaction At Ysz/gdc Interfacesmentioning
confidence: 99%
“…For example, Lu et al [56] reported that after the sintering of a YSZ electrolyte close to an LSCF pellet without physical contact at 1200 °C for 50 h, SrZrO 3 was observed at the grain boundary of the YSZ electrolyte surface, indicating the volatility of surfacesegregated Sr species. Yin et al [251] also compared the SrO activity of SrO powder with LSCF powder through annealing at 1000 °C in air for 200 h in which a YSZ sheet was placed on top of the powders without direct contact during annealing. It was reported that after annealing with SrO powder, Sr deposition was observed on the YSZ surface, whereas after annealing with LSCF powder, no Sr deposition was observed on the YSZ surface, indicating the higher SrO activity of SrO powder as compared with LSCF powder at 1000 °C.…”
Section: Sr Segregation and Reaction At Ysz/gdc Interfacesmentioning
confidence: 99%
“…To mitigate this effect, the CGO layer is often fired between 1200 and 1300 °C without full densification. Thus, the CGO layer still remains porous and permeable for volatile Sr-containing species evaporated from the LSCF electrode, such as Sr­(OH) 2 , which can diffuse to the electrolyte interface in the gas phase and react with YSZ. , Furthermore, it is technically difficult to further minimize the layer thickness via screen printing.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical degradation mechanism includes the interaction of Cr 2 O 3 with the La 2 NiO 4+ δ component of the functional layer with the formation of less active LaCrO 3 on the La 2 NiO 4+δ surface. This mechanism resembles processes of the formation of solid Sr‐Cr‐O phases (predominantly, SrCrO 4 ) in the case of LSCF electrodes 46 …”
Section: Resultsmentioning
confidence: 81%
“…This mechanism resembles processes of the formation of solid Sr-Cr-O phases (predominantly, SrCrO 4 ) in the case of LSCF electrodes. 46 A set of studies under polarization indicates the electrochemical nature of degradation: cathodic polarization increases the degradation rate, and anodic polarization decreases the degradation rate. These data are consistent with the results obtained in Reference 57.…”
Section: Mechanism Of Chromium Poisoningmentioning
confidence: 99%